Czynniki ryzyka rozwinięcia się cysty pęcherzyka filtracyjnego po operacji trabekulektomii w materiale własnym - Szaflik, Jerzy; Kamińska, Anna; Cieślik, Krzysztof; Grabska-Liberek, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The aim of the study was to evaluate the incidence of encapsulated filtering bleb at patients after trabeculectomy. We analyzed risk factors, prognosis and treatment in cases of this complication. All 857 cases of trabeculectomies performed in Department of Ophthalmology of Medical University of Warsaw in years 2001-2003 were included in the study. Twenty two cases (2,5% of all trabeculectomies) of encapsulated filtering bleb were analyzed. Twenty patients (91%) underwent surgery procedure and two patients (9%) were treated medically. The encapsulated filtering blebs occurred mainly in patients after previous ocular surgery, in eyes with episodes of earlier ocular inflammation and in patients treated with many antiglaucoma drops.